Navigating a sustainable agricultural economy in Indonesia's new capital city - Arfiah Busari; Surya Darma; Priyagus Priyagus; Tetra Hidayati; Dedy Darmawan; Dio Caisar Darma; Akhmat Rizkuna (Sustinere: Journal of Environment and Sustainability)
One of the Sustainable Development Goals (SDGs) under the second pillar emphasizes to aim to “End Hunger, Achieve Food Security and Improved Nutrition, and Promote Sustainable Agriculture”. At the same time, Indonesia is relocating its capital city to Ibu Kota Nusantara (IKN), and the demand for agricultural commodities is increasing in line with population growth. Referring to this phenomenon, this article examines the relationship between labor, employment opportunities, loan value, and entrepreneurship with expenditure and per capita income, and economic growth in the agricultural sector within the IKN region. Secondary data were obtained from government agencies for the period 2015–2023 and analyzed using time-series regression. The empirical findings highlight three important points. First, labor, entrepreneurship, and per capita expenditure positively influence economic growth. Second, these variables also have a positive impact on per capita income. Third, employment, loan value, per capita income, and economic growth are positively associated with per capita expenditure. This case study suggests that stakeholders, including policy makers, academics, businesses, and local communities, should develop more inclusive agricultural economic policies. In the long-term, such approach could help refine and expand existing conceptual frameworks.